2021
DOI: 10.1177/14759217211044116
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid artificial intelligence-based inference models for accurately predicting dam body displacements: A case study of the Fei Tsui dam

Abstract: Surveillance is a critical activity in monitoring the operation condition and safety of dams. This study reviewed the historical monitoring data of the Fei Tsui dam to determine possible influential factors for the dam body displacement and then evaluated the influencing degree of these factors by using correlation analysis. Thus, the key influential factors were identified objectively and further chosen as the input variables for numerous artificial intelligence (AI)-based inference models, including single m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
1
0
0
Order By: Relevance
“…us, this finding complies with results reported in recent studies that utilize hybrid computing models in civil engineering [119][120][121][122][123][124][125]. Although SSA has been demonstrated to be an effective swarm intelligent method used for solving various complex optimization tasks Houssein et al 2020; [76,126,127], its application in constructing sophisticated computer vision-based systems is still rare.…”
Section: Resultssupporting
confidence: 85%
“…us, this finding complies with results reported in recent studies that utilize hybrid computing models in civil engineering [119][120][121][122][123][124][125]. Although SSA has been demonstrated to be an effective swarm intelligent method used for solving various complex optimization tasks Houssein et al 2020; [76,126,127], its application in constructing sophisticated computer vision-based systems is still rare.…”
Section: Resultssupporting
confidence: 85%
“…Lin et al proposed a novel dam health monitoring model using optimized sparse Bayesian learning and sensitivity analysis, mainly for monitoring radial displacement and seepage [19]. Cheng et al compared the results of support vector machines, artificial neural networks, and hybrid artificial intelligence models in dam displacement prediction [20]. Kang et al compared the outputs of the GPR-HST model with the GPR model and concluded that the GPR approach is more effective in capturing the nonlinearity of the dam response [21].…”
Section: Related Workmentioning
confidence: 99%
“…Jia et al (2019) used the GBRT algorithm based on slope monitoring data to improve risk prevention and control [32]. Some scholars have also introduced machine-learning methods to the tailings dam risk prediction problem and achieved good results [33]. The interpretability of the model is poor because machine-learning-based methods cannot extract the significance of each influencing variable.…”
Section: Introductionmentioning
confidence: 99%